Kematian Akibat Bencana dan Pengaruhnya Pada Kondisi Psikologis Survivor:Tinjauan Teoritis Tentang Arti Penting Death Education - Yulianti Dwi Astuti (Universitas Islam Indonesia, 2007)
Any sort of accident creates a certain amount of psychological stress in anyone, but the stress becomes particularly acute when many people are killed. Varying to some extent with the individual, the immediate reactions to a disaster are shock, fear, sadness, and rage, which may even lead to a denial that the disastrous event occurred. A person’s sense of control over his or her life and many of the things that make it real and predictable are threatened by an unexpected disaster. Death is a part of life about which children and adults need to be familiar with death and understand it. Nevertheless, as with sex educa- tion, introduction of the topic of death in schools and colleges has sometimes been met with cries of alarm about the potentially damaging effects of readings, discussions, and other activities concerning this topic. Kata-kata kunci: disaster, death, psychological stress,education